Cost-effectiveness of meglumine antimoniate versus miltefosine caregiver DOT for the treatment of pediatric cutaneous leishmaniasis - Berger, Brandon A. (PLoS Negl Trop Dis, 2017)
BACKGROUND: Oral miltefosine has been shown to be non-inferior to first-line, injectable meglumine antimoniate (MA) for the treatment of cutaneous leishmaniasis (CL) in children. Miltefosine may be administered via in-home caregiver Directly Observed Therapy (cDOT), while patients must travel to clinics to receive MA. We performed a cost-effectiveness analysis comparing miltefosine by cDOT versus MA for pediatric CL in southwest Colombia. METHODOLOGY/PRINCIPLE FINDINGS: We developed a Monte Carlo model comparing the cost-per-cure of miltefosine by cDOT compared to MA from patient, government payer, and societal perspectives (societal = sum of patient and government payer perspective costs). Drug effectiveness and adverse events were estimated from clinical trials. Healthcare utilization and costs of travel were obtained from surveys of providers and published sources. The primary outcome was cost-per-cure reported in 2015 USD. Treatment efficacy, costs, and adherence were varied in sensitivity analysis to assess robustness of results. Treatment with miltefosine resulted in substantially lower cost-per-cure from a societal and patient perspective, and slightly higher cost-per-cure from a government payer perspective compared to MA. Mean societal cost-per-cure were $531 (SD±$239) for MA and $188 (SD±$100) for miltefosine, a mean cost-per-cure difference of +$343. Mean cost-per-cure from a patient perspective were $442 (SD ±$233) for MA and $30 (SD±$16) for miltefosine, a mean difference of +$412. Mean cost-per-cure from a government perspective were $89 (SD±$55) for MA and $158 (SD±$98) for miltefosine, with a mean difference of -$69. Results were robust across a variety of assumptions in univariate and multi-way analysis. CONCLUSIONS/SIGNIFICANCE: Treatment of pediatric cutaneous leishmaniasis with miltefosine via cDOT is cost saving from patient and societal perspectives, and moderately more costly from the government payer perspective compared to treatment with MA. Results were robust over a range of sensitivity analyses. Lower drug price for miltefosine could result in cost saving from a government perspective.